How to express the adsorbed CO2 with the Gibbs' thermodynamic graphical method: A preliminary study. (15th February 2020) - Li, Shuangjun; Deng, Shuai; Zhao, Li; Yuan, Xiangzhou; Yun, Heesun
Abstract: Adsorption carbon capture technology has been considered as one of the most promising technologies to control the CO2 level in the atmosphere. From the view of thermodynamics, the adsorbed-bulk gas phase equilibrium system should be well developed for accurately elaborating the mechanism of CO2 adsorption. Since thermodynamic properties of the adsorbed CO2 plays a significant role in the cyclic analysis of carbon capture technology, in this work, the Gibbs' thermodynamic graphical method was extended to the expression of thermodynamic properties of the adsorbed CO2 as a specific case study. The 3-dimensional (3D) thermodynamic surface was established to determine the thermodynamic properties of the adsorbed CO2 in the thermodynamic equilibrium state. The temperature and pressure were treated as the individual variables to calculate the thermodynamic properties of the adsorbed CO2, including the adsorption capacity, chemical potential, entropy, and internal energy. Finally, the internal energy-adsorption capacity-entropy 3D thermodynamic surface of the adsorbed CO2 was obtained by the Gibbs' thermodynamic graphical method. The thermodynamic surface established in this work will contribute and/or accelerate the research of the actual adsorption thermodynamic cycle and new findings are encouraged to be updated to our database to enhance the development on thermodynamic characteristics of the adsorption technology. Highlights: Two individual variables are needed to determine the adsorbed CO2 thermodynamic state. Calculation of adsorbed CO2 thermodynamic properties is summarized. The 3-dimensional thermodynamic surface of the adsorbed CO2 was established.